Islamic Efforts in Realizing the Sakinah Family: "Solutions to Overcome Domestic Violence (DV)" - Khairil Ikhsan Siregar; Muhammad Alif (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2025)
This paper examines the role of Islam in realizing the sakinah family as a solution to overcome domestic violence (KDRT). This study aims to identify the application of Islamic values in creating a harmonious family and preventing domestic violence. The method used is an in-depth literature study by examining various sources, both the Qur'an, hadith, and the views of scholars related to rights and obligations in family life in Indonesia. The findings of this study reveal that Islam strongly emphasizes the importance of harmony in the household, by providing clear guidance on the roles and responsibilities of each party, as well as ways to resolve conflicts peacefully and encourage problem solving through dialogue, mediation, and a compassionate approach. Therefore, the application of Islamic teachings that prioritize respect and harmony can be an effective solution in overcoming domestic violence in society.